Developmental Biology And Genetic Diversity Of Selected Neritidae In Malaysia With An Emphasis On Nerita Balteata - Chee, Su Yin (2013)
The gastropods in this study are from the genus Nerita found in the rocky and muddy intertidal zones along the coasts of Malaysia. The species diversity was analyzed, morphological descriptions were made, and barcodes of cytochrome oxidase I were generated for each of the 12 species of nerites found. The nuclear gene, ATPS-α, successfully determined the phylogenetic status of each species. Twenty-one populations of the focal species of this study, N. balteata, were sequenced for 16S rRNA gene fragments to determine the population structure of nerites found in this region. Despite geographic and oceanographic barriers and habitat boundaries, the nerites managed to maintain a homogeneous structure between Peninsular Malaysia, Sarawak, and Sabah. Genetic distances between populations were low, phylogenetic trees did not exhibit distinct clades which denoted singular populations, and network diagrams produced two major haplotypes with most populations accounted for in each.